Endovascular Perfusion Augmentation for Critical Care: Partial Aortic Occlusion for Treatment of Severe Ischemia–Reperfusion Shock. Issue 5 (May 2019) - Johnson, M. Austin; Tibbits, Emily M.; Hoareau, Guillaume L.; Simon, Meryl A.; Davidson, Anders J.; DeSoucy, Erik S.; Faulconer, E. Robert; Grayson, J. Kevin; Neff, Lucas P.; Williams, Timothy K.
ABSTRACT: Background: The resuscitation of patients in shock is materially intensive and many patients are refractory to maximal therapy. We hypothesized that partial inflation of an intra-aortic balloon, termed Endovascular Perfusion Augmentation for Critical Care (EPACC), would minimize material requirements while improving physiologic metrics. Methods: Swine underwent a 25% controlled bleed and 45 min of complete aortic occlusion to create a severe ischemia–reperfusion shock state. Animals received either standardized critical care (SCC) composed of IV fluids and norepinephrine delivered through an algorithmically controlled platform or EPACC in addition to SCC. Physiologic parameters were collected, and blood was sampled for analysis. Primary outcomes were total IV fluids and average MAP during the critical care phase. Differences ( P  < 0.05) were measured with t test (continuous data) and Wilcoxon rank-sum test (ordinal data). Results: There were no differences in baseline characteristics. There were no differences in the maximum lactate; however, animals in the EPACC group had a higher average MAP (EPACC 65 mmHg, 95% confidence interval [CI], 65–66; SCC 60 mmHg, 95% CI, 57–63; P  < 0.01) and remained within goal MAP for a greater period of time (EPACC 95.3%, 95% CI, 93.2–97.4; SCC 51.0%, 95% CI, 29.5–72.6; P  < 0.01). EPACC animals required less IV fluids when compared with the SCC group (EPACC 21 mL/kg, 95% CI, 0–42; SCC 96 mL/kg, 95% CI, 76–117; P  < 0.01). There were no differences in final lactate. Animals in the EPACC group had a higher final creatinine (EPACC 2.3 mg/dL, 95% CI, 2.1–2.5; SCC 1.7 mg/dL, 95% CI, 1.4–2.0; P  < 0.01), but there were no differences in renal cellular damage on histology ( P  = 0.16). Conclusion: Using a swine model of severe shock, the addition of EPACC to SCC significantly reduced fluid resuscitation requirements and improved blood pressure. This is the first description of a new therapy for patients in refractory shock or in resource-limited settings. Abstract : Supplemental Digital Content is available in the text